2017
DOI: 10.4168/aair.2017.9.6.491
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Respiratory Viral Infections in Korean Adult Asthmatics With Acute Exacerbations: Comparison With Those With Stable State

Abstract: PurposeViral infections are involved in ~50% of exacerbations among Caucasian adult asthmatics. However, there have been few reports on the causative virus of exacerbations in Korean adult asthmatics. Thus, we compared frequencies and types of viruses between lower respiratory tract illnesses (LRTIs) with exacerbations (exacerbated LRTIs) and those without exacerbations (stable LRTIs) to evaluate contribution of respiratory viruses to exacerbations.MethodsViral RNA was extracted from sputum using the Viral Gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…For instance, the prevalence rates of parainfluenza and influenza viruses in Brazil were 30% and 21%, respectively [26]. Moreover, in a study conducted in Korea between 2 groups of patients with severe and stable con-ditions, the parainfluenza virus was the most common virus (16.8%) detected [27].…”
Section: Discussionmentioning
confidence: 98%
“…For instance, the prevalence rates of parainfluenza and influenza viruses in Brazil were 30% and 21%, respectively [26]. Moreover, in a study conducted in Korea between 2 groups of patients with severe and stable con-ditions, the parainfluenza virus was the most common virus (16.8%) detected [27].…”
Section: Discussionmentioning
confidence: 98%
“…A study conducted by Ki-Hyun Seo et al detected RV in 45.5% of the LRTs of asymptomatic stable asthma patients. Moreover, those infected with rhinovirus are more likely to have more severe LRT infections, with longer-lasting symptoms [ 46 ]. Few studies have shown that RV induces expression of major epithelial mucin MUC5AC, leading to mucus hypersecretion.…”
Section: Asthmamentioning
confidence: 99%
“…Thus, IFN deficiency results in more severe and prolonged respiratory symptoms in asthmatic patients. The influenza virus is another common virus in asthmatic patients [ 46 ]. During the influenza virus pandemics in 2009, asthma was one of the risk factors associated with increased hospitalization among children and adults.…”
Section: Asthmamentioning
confidence: 99%
“…In subjects with LOA, airway remodeling can be either pathological or physiological due to aging-related structural changes in the airway 2,8 . Additionally, viral respiratory infections can worsen airway remodeling in adult asthma 9 . Respiratory viral infections induce the release of proinflammatory cytokines such as interleukin (IL)-6 and IL-8 from human airway epithelial cells (HAECs) and initiate cell recruitment, which amplifies airway inflammation and subsequent airway remodeling, such as long-term alterations in airway structures and functions in asthma 10,11 .…”
Section: Introductionmentioning
confidence: 99%